High-mobility β-Ga2O3() single crystals grown by edge-defined film-fed growth method and their Schottky barrier diodes with Ni contact - Oishi, Toshiyuki; Koga, Yuta; Harada, Kazuya; Kasu, Makoto (Applied physics express, 2015)
High-Hall-electron-mobility and high-performance Schottky barrier diodes for edge-defined fed-grown () β-Ga2O3 single crystals have been demonstrated. A high electron mobility of 886 cm2/(V·s) at 85 K was obtained. By theoretical specific scattering mechanisms, it was found that the electron mobility for >200 K is limited by optical phonon scattering and that for <100 K by ionized impurity scattering. On Schottky barrier diodes with Ni contacts, the current density for the forward voltage was 70.3 A/cm2 at 2.0 V, and a nearly ideal ideality factor of 1.01 was obtained.